The performance of the truncated mixed control chart - Campos Leoni, Roberto [UNESP]; Branco Costa, Antonio Fernando (Taylor & Francis, 2019)
When the mixed chart proposed by Aslam et al. (2015) is in use, the sample items are classified as defective or not defective and, depending on the number of defectives, the quality characteristic X of the sample items are also measured. In this case, an Xbar chart decides the state of the process. The previous conforming/non-conforming classification truncates the X distribution and, because of that, the mathematical development to obtain the ARLs is complex. Aslam et al. (2015) didn’t pay attention to the fact that the X distribution is truncated and, due to that, they obtained incorrect ARLs.
Keywords: average sample size; inspection by attribute and by variable; Mixed chart; truncated distribution